It is not Appendicitis! It is Appendicitis Epiploica, the Great Pretender - Nobi, Farah; Ali, Shayda; Rahman, Md Mostafizur; Lodi, Russel Ahmed Khan; Basunia, Mohammad Arman Zahed; Shahriar, Sazzad; Rahman, Shamsur; Rouf, Hasan Mohammad Abdur; Paul, Tapesh Kumar (Journal of Surgical Sciences, 2020)
Appendicitis epiploica or epiploicae appendagitis, an uncommon cause of abdominal pain, is usually per-operatively diagnosed. The pedunculated fat-filled small pouches or appendices epiploicae on the serosal surface of the colon often become twisted and sometimes spontaneous thrombosis occurs. Such events lead to ischemia and inflammation at the base of the fatty lobes i.e., Appendicitis epiploicae. Symptoms include sharp localized pain in either iliac fossae and in some cases there is elevated temperature and white blood cell count. In a quarter of the patients there is rebound tenderness and very rarely nausea and vomiting, diarrhoea or constipation. This condition is more common among middle aged males and given its non-specific symptoms. It is usually confused with other more common conditions such as Meckel’s diverticulitis and appendicitis. Less than 8% of patients suspected of having appendicitis or diverticulitis are found to actually have appendicitis epiploicae. Here we report two extremely rare cases of appendicitis epiploica in Bangladesh. Journal of Surgical Sciences (2019) Vol. 23(2): 95-97